(untitled) (Revista Contexto & Educação, 2023)
This study presents a section of the activities developed by Special Education in a Basic Education School from a municipal teaching network from an inland city of the state of Rio Grande do Sul, Brazil, in which one of the authors works as a Special Education teacher. The study aims to identify the extent to which Collaborative Teaching enhances inclusive school education in Basic Education. For such, it was opted for a qualitative research, of the participant type, with descriptive analysis. It was argued that the pedagogical practices carried out from the perspective of the Collaborative Teaching imply the relationship between the Special Education teacher and the regular classroom, positively collaborating in the teaching-learning process of all students, improving learning and contributing to the effectiveness of the school inclusion process. Among the conclusions, it is observed that the Collaborative Teaching can contribute and enhance inclusive school Education, as long as it finds an open and accessible context for the realization of this teaching practice. Among the observed contexts throughout the research, the possibility of the exchanges between professors and students and the democratization of the teaching-learning process stands out.